The countervailing power hypothesis when dominant retailers function as sales promoters - Noriaki Matsushima; Shohei Yoshida (Osaka University, Institute of Social and Economic Research (ISER), 2016)
We consider a downstream oligopoly model with one dominant and several fringe retailers, who purchase a manufacturing product from a monopoly supplier. We then examine how the supplier's outside option influences the relation between the dominant retailer's bargaining power and the equilibrium retail price. If the market demand shrinks due to a breakdown of bargaining between the supplier and the dominant retailer, who works as a sales promoter for the product, there is a negative relation between the bargaining power and the retail price. Furthermore, retailers' efficiency improvements increase the retail price if the dominant retailer's bargaining power is strong.
Keywords: L13; D43; 330; Countervailing power; Buyer power; Dominant retailer; Two-part tariff